Shape-memory implants in abdominal surgery - G. Ts. Dambayev; V. E. Gyunter; M. M. Soloviyov; V. R. Latypov; O. A. Fatyushina; Ye. G. Dambayeva; Ye. A. Avdoshina; M. A. Sharayevsk (Бюллетень сибирской медицины)
Here are represented our results according to making and clinical using of different TiNi devices for treatment of digestive system diseases. Constructions for perfoming of compression anastomoses, cliping of tubular structures during laparoscopic operations and perforated ulcer plastic. Materials of experimental investigations and clinic experience of 220 cases treatment are represented.